Development of Simple, Easy and Inexpensive Online System For List Of Proposal Assessment Credit Score of Widyaiswara - Sri Mahendra Satria Wirawan (Jurnal Teknologi Informasi dan Pendidikan, 2020)
The current process of proposing and calculating credit number for Widyaiswara is felt to require an exceedingly difficult effort. Many costs must be incurred, especially to hold office stationery such as printing equipment, paper, ink, binder clips, and others. The next issue is how to provide a relatively large number of proposal files and a place for verification and evaluation. After the research is finished, the problem arises again when it will destroy the documents that have been examined. This condition causes waste generation which is not environmentally friendly. An alternative solution for this is to use an online system of calculating credit numbers. However, the development and use of online system applications require considerable development, maintenance, and development costs. Based on research conducted using Microsoft Excel software combined with several software that provides unpaid facilities, a credit score calculation system application can be built for Widyaiswara that is simple, easy, and inexpensive. The results of trials conducted on the calculation of Widyaiswara BPSDM credit figures in DKI Jakarta Province gave very satisfying results, especially on increasing the speed of time and accuracy of proposals and assessments.